2014
DOI: 10.1007/s40620-014-0163-z
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic and short-term prognostic utility of plasma pro-enkephalin (pro-ENK) for acute kidney injury in patients admitted with sepsis in the emergency department

Abstract: Use of pro-ENK in septic patients can detect the presence and severity of AKI. Moreover, pro-ENK is highly predictive of short-term mortality and could enable early identification of patients at risk of death.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
69
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(84 citation statements)
references
References 35 publications
10
69
0
1
Order By: Relevance
“…In our opinion, acute renal failure may have resulted from rhabdomyolysis in our patient. Promising markers such as neutrophil gelatinase-associated lipocalin and pro-enkephalin may be useful in these patients to determine both presence and prognosis of renal failure 11, 12…”
Section: Discussionmentioning
confidence: 99%
“…In our opinion, acute renal failure may have resulted from rhabdomyolysis in our patient. Promising markers such as neutrophil gelatinase-associated lipocalin and pro-enkephalin may be useful in these patients to determine both presence and prognosis of renal failure 11, 12…”
Section: Discussionmentioning
confidence: 99%
“…This study showed a convincing sevenfold decrease in the requirement of renal replacement therapy and a 2.4fold decrease in mortality in patients receiving supportive therapy on the day of the alert compared to patients receiving delayed supportive therapy (day 1 or later). 10,15,19 We are therefore confident, that our baseline PENK results will apply to other populations. 23 Potential limitations of the current study merit consideration.…”
Section: Discussionmentioning
confidence: 77%
“…22 Of note, this intervention was based on the review of serial creatinine measurements, and the additional 24-hour window of opportunity provided delta PENK could potentially provide even bigger benefits. However, while recent data suggest, that including urine output criteria into the AKI definition might increase the AKI incidence, 24 most previously published studies assessing the predictive potential of AKI biomarkers in the non-ICU setting, also opted to exclude the urine output criteria for AKI diagnosis 10,15,25 as measuring urine output in a non-ICU setting is tedious and error prone. First, our study has a moderate number of patients and only few developed AKI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Promising markers such as neutrophil gelatinase-associated lipocalin and pro-enkephalin may be useful in these patients to determine both presence and prognosis of renal failure. 11,12 Reported cardiovascular complications of bee stings include acute myocardial infarction in patients with normal and abnormal coronary arteries. 13,14 We suggested that in our patient, ventricular dysrhythmia seems to be related to the release of vasoactive amines and thrombogenic substances that are in the hymenopterans venom, the former able to produce vasospasm, the latter able to ventricular dysrhythmia.…”
Section: E8mentioning
confidence: 99%